Various surgical methods of impacted maxillary canine exposure: A case series - Meenalochani T Balasuppramaniem; A Anitha; B Manovijay; Saranyan Ravi (Wolters Kluwer Medknow Publications, 2023)
Impacted tooth is often a common problem in dentistry. Maxillary canines are seen impacted most commonly in patients undergoing orthodontic treatment without reaching the line of occlusion. These impactions are commonly due to physical obstructions and the difference in the direction of movement of the tooth. Canines are the cornerstones for esthetic smile and functional occlusion. Hence, surgical exposure of these impacted canines, guiding them toward the line of occlusion, plays a very important role in the maintenance of the health of periodontium. A series of cases are discussed on various techniques that can be used in guiding the direction or altering the direction of impacted canines to bring them into a proper occlusion without disturbing the health of periodontium.